"Switching on" the single-molecule magnet properties within a series of dinuclear cobalt(iii)–dysprosium(iii) 2-pyridyloximate complexes. Issue 43 (17th October 2017) - Polyzou, C. D.; Koumousi, E. S.; Lada, Z. G.; Raptopoulou, C. P.; Psycharis, V.; Rouzières, M.; Tsipis, A. C.; Mathonière, C.; Clérac, R.; Perlepes, S. P.
Abstract : Single-molecule magnet properties are "switched on" within a family of isostructural dinuclear cobalt(iii )/dysprosium/2-pyridyloximate complexes. Abstract : The use of 2-pyridinealdoxime (paoH), methyl 2-pyridyl ketone oxime (mepaoH), phenyl 2-pyridyl ketone oxime (phpaoH) and pyridine-2-amidoxime (NH2 paoH) for the synthesis of dinuclear Co III /Dy III complexes is described in the absence or presence of an external base. Complexes [CoDy(pao)3 (NO3 )3 ] (1 ), [CoDy(mepao)3 (NO3 )3 ] (2 ), [CoDy(phpao)3 (NO3 )3 ] (3 ) and [CoDy(NH2 pao)3 (NO3 )3 ]·3MeOH (4 ·3MeOH) have been isolated and their structures have been determined by single-crystal X-ray crystallography. The complexes crystallize in non-centrosymmetric (2, 3 ) or centrosymmetric (1, 4 ·3MeOH) trigonal space groups and form a family of triply-oximate bridged dinuclear Co(iii )–Dy(iii ) complexes. The crystals of1, 3 and4 ·3MeOH contain mixtures of Δ and Λ enantiomers, whereas complex2 is enantiomerically pure (Λ). A 3-fold crystallographic axis ( C 3 ) passes through two metal ions in all complexes. The low-spin Co III and Dy III ions are bridged by three oximate groups belonging to the η 1 :η 1 :η 1 :μ 2-pyridyloximate ligands. The Co III centre is octahedrally coordinated by the six nitrogen atoms of the deprotonated organic ligands in a facial arrangement. The Dy III centre is bound to an O9 set of donor atoms, its coordination sphere being completed by three bidentate chelating nitrato groups. The coordination polyhedron around Dy III in1 is best described as the Johnson tricapped trigonal prism, while the coordination geometries of the Dy III centres in2, 3 and4 ·3MeOH are best described as consisting of spherical tricapped trigonal prismatic coordination polyhedra. The spectroscopic data of the complexes are also reported and discussed in the infra-red region in terms of the coordination modes of the ligands involved. The magnetic properties of these complexes were studied between 300 and 1.8 K revealing mainly the depopulation of the Dy III m j sublevels of the ground 6 H15/2 state. The intrinsic magnetic anisotropy of the Dy III centers is clearly observed by the non-superimposed magnetization ( M ) versus H / T data, but single-molecule magnet (SMM) properties were detected only for the mepao − -containing complex2 . The origin of these properties in2 is critically discussed and supported by computational studies.